Terrestrial and extraterrestrial altruism - Rolston, Holmes, 1932-2025, author; Springer-Verlag Berlin Heidelberg, publisher (Colorado State University. Libraries, 2014)
How Earthbound are values and ethics? We humans enjoy a surprising transcendence of localized body and place. We are always situated somewhere, but it does not follow that all our knowledge is situational. True, science is a human enterprise. True, ethics is a human activity - even biologically-based. But can we expect to share some of our science and ethics with extraterrestrials? Perhaps in the search for extraterrestrial intelligence, the question to ask is not about the value of pi, or the atomic number of carbon. A more revealing test might be to ask whether one should tell the truth, keep promises, or be just. The Golden Rule may be as universally true as is the theory of relativity.
Keywords: altruism; ethics; extraterrestrials; Golden Rule; promises; justice; truth-telling